2017
DOI: 10.1016/j.stemcr.2017.05.028
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of CDK5 Alleviates the Cardiac Phenotypes in Timothy Syndrome

Abstract: SummaryL-type calcium channel CaV1.2 plays an essential role in cardiac function. The gain-of-function mutations in CaV1.2 have been reported to be associated with Timothy syndrome, a disease characterized by QT prolongation and syndactyly. Previously we demonstrated that roscovitine, a cyclin-dependent kinase (CDK) inhibitor, could rescue the phenotypes in induced pluripotent stem cell-derived cardiomyocytes from Timothy syndrome patients. However, exactly how roscovitine rescued the phenotypes remained uncle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(41 citation statements)
references
References 34 publications
0
40
1
Order By: Relevance
“…Although roscovitine rescued the electrophysiological abnormality in LQTS8 hiPSC-CMs, the exact mechanism by which it restored cardiac function was not clear. In a separate study 104 , it was shown that roscovitine exhibits its therapeutic effects in part by inhibiting CDK5, a key mediator involved in the regulation of Ca V 1.2 channels in CMs. These studies provide mechanistic insights into the regulation of Ca V 1.2 and the development of future therapeutics for Timothy syndrome patients 104 .…”
Section: Long Qt Syndromementioning
confidence: 99%
See 1 more Smart Citation
“…Although roscovitine rescued the electrophysiological abnormality in LQTS8 hiPSC-CMs, the exact mechanism by which it restored cardiac function was not clear. In a separate study 104 , it was shown that roscovitine exhibits its therapeutic effects in part by inhibiting CDK5, a key mediator involved in the regulation of Ca V 1.2 channels in CMs. These studies provide mechanistic insights into the regulation of Ca V 1.2 and the development of future therapeutics for Timothy syndrome patients 104 .…”
Section: Long Qt Syndromementioning
confidence: 99%
“…To date, several groups have successfully modeled CPVT using the hiPSC platform 106108 . CPVT1 patient-specific hiPSC-CMs carrying the F2483I mutation in the RYR2 107 recapitulated DADs after catecholaminergic stimulation while Ca 2+ imaging studies revealed higher amplitudes and longer durations of spontaneous Ca 2+ release at basal state compared to control hiPSC-CMs.…”
Section: Catecholaminergic Polymorphic Ventricular Tachycardiamentioning
confidence: 99%
“…In general, it appears that macroscopic gating changes observed in heterologous expression systems reproduce the changes observed in native cells reasonably well. This is evident from animal models harboring specific human mutations ( Drum et al, 2014 ; Rose et al, 2014 ; Calorio et al, 2019 ) or from human cells differentiated from patient-derived induced pluripotent stem cells (iPSCs; e.g., neuron-like or cardiomyocyte-like cells; Yazawa et al, 2011 ; Krey et al, 2013 ; Song et al, 2017 ; Estes et al, 2019 ; Chavali et al, 2019 ). In contrast, it is less clear how well changes of current density and of channel protein expression observed in heterologous overexpression systems reflect changes of current density in native tissues ( Chavali et al, 2019 ).…”
Section: Gain- and Loss- Of Ca 2+ -Channel Functiomentioning
confidence: 99%
“…Recently, crystal structures and homology modeling provided compelling evidence that this region binds SH3-domain-containing proteins (e.g., STAC) and LQT8 variants are expected to weaken this interaction ( Mellor et al, 2019 ). Another example is the slow inactivation of the Cav1.2-G406R type 1 mutation, which appears to be mediated by cyclin-dependent kinase 5 (CDK-5; Song et al, 2017 ).…”
Section: Gain- and Loss- Of Ca 2+ -Channel Functiomentioning
confidence: 99%
“…60 Other study also demonstrated that roscovitine exerts its therapeutic effects partly by inhibiting CDK5, providing new evidences in regulating cardiac Cav1.2 channels and developing therapeutics for managing TS patients. 101…”
Section: Treatment and Managementmentioning
confidence: 99%